A novel CRDT-based synchronization method for real-time collaborative CAD systems. (October 2018) - Lv, Xiao; He, Fazhi; Cheng, Yuan; Wu, Yiqi
Highlights: A novel CRDT-based method to maintain eventual consistency for real-time collaborative CAD systems. A conflict detection mechanism is presented to detect relations of feature-based CAD operations. To ensure the consistency of shared CAD model and preserve the intentions of collaborative designers. Case studies of collaborative modeling procedures verify the proposed method. Abstract: CRDT (Conflict-free Replicated Data Type) has been proposed as an alternative synchronization mechanism for collaborative text editing systems in recent years. However, CRDT-based synchronization methods for collaborative systems with sophisticated objects, such as collaborative CAD (Co-CAD) systems, are rarely investigated in previous literatures. How well CRDT-based synchronization methods for Co-CAD systems could perform remains unknown. This paper presents a novel CRDT-based synchronization method to maintain eventual consistency for the feature-based CAD model. Firstly, three operation relations are defined as the dependency-conflict relation, the mutual exclusive relation and the compatible relation in context of the feature-based CAD systems. Secondly, a feature-based conflict detection mechanism is proposed to detect the three relations. Thirdly, a feature-based conflict resolution approach under the CRDT framework is presented to solve the conflicts. Fourthly, the time complexity and the space complexity are analyzed in theory. Finally, case studies of collaborative modeling procedures verify the correctness and feasibility of the proposed method.